2023
DOI: 10.18280/ijsdp.180106
|View full text |Cite
|
Sign up to set email alerts
|

Public Administration of Planning for the Sustainable Development of the Region in the Context of Total Digitalization

Abstract: The main purpose of the article is to form a mechanism for public administration of the planning system for the sustainable development of the region in the context of digitalization. To achieve the goals set, the method of graphical construction of the functional mechanism was used. The use of this technique made it possible to depict in detail the process of achieving the final goal. In addition, a significant advantage of this model is that the modeling system takes into account the functional relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Another group of scientists [19][20][21], using absolute indicators of descriptive statistics when conducting a comparative analysis of international trade, found that this leads to false conclusions, since the volumes of export and import operations (million dollars) for different countries differ significantly. However, with the help of relative indicators, one can compare the variation in the data characterizing the trade of different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of scientists [19][20][21], using absolute indicators of descriptive statistics when conducting a comparative analysis of international trade, found that this leads to false conclusions, since the volumes of export and import operations (million dollars) for different countries differ significantly. However, with the help of relative indicators, one can compare the variation in the data characterizing the trade of different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Варто зауважити, що в контексті соціального розвитку під час глобалізаційних змін і воєнного стану реалізація публічного управління ґрунтується на кількох важливих принципах (табл.1). Джерело: складено авторами на основі [2; [9][10][11] Отже, ці принципи визначають ефективний фундамент для впровадження публічного управління в умовах складних соціальних і геополітичних викликів.…”
Section: )unclassified
“…Кадрова безпека на підприємстві включає різні заходи та протоколи, спрямовані на захист персоналу, активів та інформації організації від внутрішніх та зовнішніх загроз. За своєю суттю кадрова безпека включає реалізацію політик та процедур, які гарантують, що тільки авторизовані особи мають доступ до конфіденційних даних та ресурсів, тим самим зводячи до мінімуму ризик витоку даних, шпигунства, саботажу та інших інцидентів безпеки [1][2]. Сутність кадрової безпеки полягає у створенні безпечного робочого середовища, в якому співробітники почуваються в безпеці, цінуються та готові захистити інтереси підприємства.…”
Section: Human Resources Management In the Personnel Security System:...unclassified